2012
DOI: 10.1111/j.1551-2916.2012.05358.x
|View full text |Cite
|
Sign up to set email alerts
|

N + Ni Codoped Anatase TiO2 Nanocrystals with Exposed {001} Facets Through Two‐Step Hydrothermal Route

Abstract: This study introduces a facile and novel route to synthesize the N + Ni codoped anatase TiO2 nanocrystals with exposed {001} facets through two‐step hydrothermal reaction. The microstructures, chemical compositions, and photocatalytic properties of the codoped TiO2 were characterized using X‐ray diffractometer, high‐resolution transmission electron microscopy, X‐ray photoelectron spectroscopy, UV‐vis spectrometry, and photoluminescence emission spectra. The experimental results revealed that (i) the elements N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Metal or non-metal ions doping of T001 can tune its electronic structure and thus obtain visible-light-responsive photocatalysts [11][12][13][14]. However, the dopants can easily become the recombination centers for charge carriers and lower stability of the doped materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metal or non-metal ions doping of T001 can tune its electronic structure and thus obtain visible-light-responsive photocatalysts [11][12][13][14]. However, the dopants can easily become the recombination centers for charge carriers and lower stability of the doped materials.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the generated holes could move into the VB of ZnO from anatase. Such a coupled effect among ZnO-anatase/rutile multiple-component interface could retard the occurrence of recombination between electrons and holes [71][72][73][74][75][76]. This effi cient charge separation prolongs the lifetime of the charge carriers and enhances the photocatalytic effi ciency of ZnOTiO 2 nanocomposite in comparison with to pure TiO 2 photocatalyst.…”
Section: [ ( )/ ( )]mentioning
confidence: 99%
“…Zhang et al [38] reported that Ni-N co-doping facilitates the separation of photo-generated carriers and enhances the photo-oxidation or photo-reduction activity.…”
Section: Introductionmentioning
confidence: 98%